2014
DOI: 10.1515/revneuro-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Candidate biomarkers of multiple system atrophy in cerebrospinal fluid

Abstract: Multiple system atrophy (MSA) is a neurodegenerative disease that presents as an autonomic dysfunction in combination with varying degrees of parkinsonism and cerebellar ataxia. It comprises a pathologically widespread neuronal loss accompanied by gliosis in the basal ganglia, cerebellum, pons, inferior olivary nuclei, and spinal cord. As a rapidly progressive disorder, MSA develops with autonomic dysfunction and mobility problems in several years. These autonomic and motor function impairments severely disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Moreover, we found that chronic hypoxia can enhance the γ‐secretase activity to promote Aβ production through the downregulation of the DNA methyltransferase 3b to reduce the methylation at CpG sites in promoter region of genes of γ‐secretase components, indicating that chronic hypoxia can aggravate AD pathology through epigenetic modifications 5 . On the other hand, chronic hypoxia may upregulate protein kinases, including GSK‐3β and CDK5, and suppress phosphatase, PP2A, leading to an enhanced tau phosphorylation 48,49 . Because hypoxia is involved in AD pathogenesis, hyperbaric oxygen treatment targeting hypoxia may be helpful to delay or ameliorate the progression of AD.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, we found that chronic hypoxia can enhance the γ‐secretase activity to promote Aβ production through the downregulation of the DNA methyltransferase 3b to reduce the methylation at CpG sites in promoter region of genes of γ‐secretase components, indicating that chronic hypoxia can aggravate AD pathology through epigenetic modifications 5 . On the other hand, chronic hypoxia may upregulate protein kinases, including GSK‐3β and CDK5, and suppress phosphatase, PP2A, leading to an enhanced tau phosphorylation 48,49 . Because hypoxia is involved in AD pathogenesis, hyperbaric oxygen treatment targeting hypoxia may be helpful to delay or ameliorate the progression of AD.…”
Section: Discussionmentioning
confidence: 94%
“…Soluble forms of Nrps have been previously reported in physiological and pathological contexts. In particular, Nrp1 in the CSF was proposed to be associated with Alzheimer’s disease and aging in humans ( 40 , 41 ). Soluble forms of Nrps in the CSF could arise from splice variants encoding forms devoid of transmembrane domains, similar to those previously described for both Nrp1 and Nrp2 ( 17 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble forms of Nrps have been previously reported in physiological as well as pathological contexts 20 . Particularly, Nrp1 in the CSF was proposed to be associated with Alzheimer disease and aging in humans 48,49 . Soluble forms of Nrps in the CSF could arise from splice variants encoding forms devoid of transmembrane domains, like those previously described for both Nrp1 and Nrp2 19,50 .…”
Section: Discussionmentioning
confidence: 99%